Exploring teaching methods for middle school English vocabulary in China: Based on observation of high-quality lessons in people’s education edition - Dai, Yuqing; Su, Yujie; Li, Xueyan (Global Journal of Social Sciences Studies, 2024)
This study investigates the methodologies used in teaching vocabulary in middle school English classrooms, focusing on the interconnections among class types, parts of speech, teaching stages, and methods. By combining offline classroom observations with a review of 99 high-quality online lessons from the People’s Education Edition, the research provides a comprehensive comparison of vocabulary instruction practices. The findings reveal that vocabulary instruction is often embedded within broader lessons on listening and speaking, reading, writing, and grammar rather than being addressed in dedicated sessions, and that there is significant variability among teachers in core vocabulary selection and instructional approaches. The study concludes that there is a lack of consistent and dedicated vocabulary teaching methods across different class types. This research offers valuable insights for educators to develop more targeted and effective vocabulary teaching strategies, aiming to improve vocabulary acquisition among middle school students.